Massive Pulmonary Thromboembolism in a Pregnant Woman Treated with Systemic Thrombolysis in a Resource-Limited Setting: Case Report - Coutinho, Inóspita; Dembi, Lídia; Manuel, Edgar; Jeremias, António; Frederico, Elsa; Sampaio, Antónia; André, Kavungo; Pinto, Evelise; Napato, Agostinho; Ngola, Edna; Almeida, Maria; Ulica, Ernesto; et al. (Brazilian Journal of Case Reports, 2026)
Pulmonary thromboembolism (PTE) is a condition characterized by obstruction of the pulmonary arterial circulation by a thrombus, usually originating from deep vein thrombosis (DVT) of the lower limbs. PTE is one of the leading causes of maternal mortality, and its diagnosis and management are particularly challenging during pregnancy. Systemic thrombolysis is considered a relative contraindication in pregnancy due to the risk of maternal and fetal hemorrhagic complications; however, it may be the only therapeutic option in cases of massive PTE with hemodynamic instability. We report the case of a 32-year-old pregnant woman at 16 weeks of gestation who presented with deep vein thrombosis associated with extensive pulmonary thromboembolism, progressing to obstructive shock, and was treated with systemic thrombolysis using alteplase. The patient showed favorable clinical evolution, without hemorrhagic complications, resulting in satisfactory maternal and fetal outcomes. This case highlights the diagnostic and therapeutic challenges of PTE during pregnancy and reinforces that systemic thrombolysis may be an effective rescue therapy in situations of hemodynamic instability, even in resource-limited settings.